Desenvolvimento de métodos por cromatografia líquida de alta eficiência muldimensional para validação do uso do biorreator gliceraldeído-3-fosfato desidrogenase de Trypanosoma cruzi para triagem de inibidores - Moraes, Marcela Cristina de (Universidade Federal de São Carlos, 2008)
This work reports the quantification of NADH formed by an immobilized enzyme reactor (IMER) of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) of T. cruzi using multidimensional high-performance liquid chromatography. For this, The IMER was used in the first dimension while an analytical C8 column was used in the second dimension. The conditions of the pre-treatment of the fused silica capillary tubes and the covalent immobilization of the enzyme into the capillary were successfully optimized, resulting in increased enzymatic activity and stability. Kinetic studies for the T. cruzi GAPDH-IMER were carried out to verify the influence of the immobilization over the enzyme affinity for the substrate and cofactor. The kinetic results for the IMERs of human and parasite GAPDH enzymes were compared to those obtained with the enzymes in solution, and showed that the covalent immobilization method used affected mainly the affinity of the human enzyme for the substrate. The human and parasite GAPDH-IMERs were employed for the ligand screening. The ligands recognized by the IMERs were the same identified by the enzymes in solution, showing that the immobilized enzymes kept the ability of recognizing the activity compounds modulators. The IMERs demonstrated to be a useful tool also for inhibitors binding reversibility characterization. In view of the high costs and difficulties involved on enzyme purification, the methods described in this work represents a valuable way of preserving enzyme activity and carrying out a variety of biochemical experiments.
Multidimensional high-performance liquid chromatography methods development for validating the employment of an immobilized enzyme reactor of glyceraldehyde-3-phosphate dehydrogenase of Trypanosoma cruzi for inhibitors screening
Keywords: Cromatografia líquida de alta eficiência; Imobilização de enzimas; Inibidores enzimáticos; Chagas, Doença de; GAPDH; CIENCIAS EXATAS E DA TERRA::QUIMICA